Association between fruit and vegetable intake and body mass index of postgraduate students at the Faculty of Health Sciences, Universiti Kebangsaan Malaysia - Teoh , Rui Fen; Yaacob, Norhasniza; Musa, Sitti Junaina; Zakaria, Muhammad Asyaari; Lau, Hui Yuan; Leong, Wun Chin; Mohd Saat, Nur Zakiah; Masre, Siti Fathiah (Life Sciences, Medicine and Biomedicine, 2021)
Background: The Malaysian Dietary Guidelines recommended that at least two servings of fruits and three servings of vegetables be consumed daily. However, is there a relationship between daily fruit and vegetable intake and body mass index (BMI)? The aim of this study was to identify the relationship between fruit and vegetable intake and BMI among postgraduate students in the health sciences. Methodogy: A cross-sectional study was conducted at the Faculty of Health Sciences, Universiti Kebangsaan Malaysia. 44 postgraduate students from the 2019/2020 batch of health sciences took partn in this study. Respondents were asked to complete three parts of the questionnaire: socio-demographic data, anthropometric measurements, and self-administered questions. Results: The majority of respondents are female (n=44, 77.3%), and they are mainly Malay (n=22, 50.0%). The average BMI of all respondents is 23.76±4.83. This study found that majority of respondents did not meet the recommended daily fruit (n=31, 70.5%) and vegetable intake (n=23, 52.3%). Discussion: The study discovered a significant relationship (p<0.05) between age and daily vegetable intake. However, there was no significant relationship (p>0.05) between gender, age, BMI, waist circumference, and daily fruit intake. Moreover, neither daily fruit nor vegetable intake predicted changes in BMI. Conclusion: This study found that the consumption of fruits and vegetables among postgraduate students was unsatisfactory and lower than recommended guidelines.